FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN AKUNTANSI PADA PUSKESMAS DI KOTA YOGYAKARTA - Muhammad Alfi Satia Pratama; Fajar Satriya Segarawasesa (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Accounting fraud is an act of fraud committed by an individual or companygroup for profit. Acts of fraud can be bad for investors as well as,even other stakeholders.This study aims to empirically test the effectiveness of the internal control system, empirically the effectiveness of information asymmetry, empirically the effectiveness of conformity compensation, empirically the effectiveness of religiosity, empirically the effectiveness of implementationGood Corporate Governance accounting at the health center in the city of Yogyakarta. The population in this study were all health centers in the city of Yogyakarta and the sample taken in this study was 36 sample consisted of heads of Administrative Sub-divisions and Financial Staff. The research method uses quantitative methods using primary data obtained from questionnaires that are distributed randomlyoffline. The data analysis technique used is descriptive statistical analysis technique with the programStatistical Program for Social Science (SPSS) Version 26. The results of the study show that the internal control system, information asymmetry, compensation suitability, religiosity and implementation Good Corporate Governance does not affect the tendency of accounting fraud at the health center in the city of Yogyakarta.